The environment, the tick, and the pathogen – It is an ensemble - Couret, Jannelle; Schofield, Samantha; Narasimhan, Sukanya (Frontiers in Cellular and Infection Microbiology, 2022)
Ixodes scapularis is one of the predominant vectors of Borrelia burgdorferi, the agent of Lyme disease in the USA. The geographic distribution of I. scapularis, endemic to the northeastern and northcentral USA, is expanding as far south as Georgia and Texas, and northwards into Canada and poses an impending public health problem. The prevalence and spread of tick-borne diseases are influenced by the interplay of multiple factors including microbiological, ecological, and environmental. Molecular studies have focused on interactions between the tick-host and pathogen/s that determine the success of pathogen acquisition by the tick and transmission to the mammalian host. In this review we draw attention to additional critical environmental factors that impact tick biology and tick-pathogen interactions. With a focus on B. burgdorferi we highlight the interplay of abiotic factors such as temperature and humidity as well as biotic factors such as environmental microbiota that ticks are exposed to during their on- and off-host phases on tick, and infection prevalence. A molecular understanding of this ensemble of interactions will be essential to gain new insights into the biology of tick-pathogen interactions and to develop new approaches to control ticks and tick transmission of B. burgdorferi, the agent of Lyme disease.